2021
DOI: 10.1097/cce.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Checklists Improve Team Performance During Simulated Extracorporeal Membrane Oxygenation Emergencies: A Randomized Trial

Abstract: Objectives: Extracorporeal membrane oxygenation–related complications are potentially catastrophic if not addressed quickly. Because complications are rare, high-fidelity simulation is recommended as part of the training regimen for extracorporeal membrane oxygenation specialists. We hypothesized that the use of standardized checklists would improve team performance during simulated extracorporeal membrane oxygenation emergencies. Design: Randomized sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Half of the studies (50%) included multiple disciplines ( 16 33 ), most frequently including physicians and nurses. More than one-third (36%) of studies included trainee physician ( 16 , 19 , 21 , 24 , 25 , 29 , 33 39 ), and four studies included healthcare students ( 26 , 40 – 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Half of the studies (50%) included multiple disciplines ( 16 33 ), most frequently including physicians and nurses. More than one-third (36%) of studies included trainee physician ( 16 , 19 , 21 , 24 , 25 , 29 , 33 39 ), and four studies included healthcare students ( 26 , 40 – 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Half of the studies (50%) included multiple disciplines ( 16 33 ), most frequently including physicians and nurses. More than one-third (36%) of studies included trainee physician ( 16 , 19 , 21 , 24 , 25 , 29 , 33 39 ), and four studies included healthcare students ( 26 , 40 – 42 ). Of uniprofessional studies listing target audiences, 11% targeted ECMO specialists ( 43 46 ), 8% targeted nurses ( 47 49 ), 3% targeted paramedics ( 50 ), and 14% targeted physicians ( 34 , 36 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, investigators employed a randomized trial that demonstrated improved team performance, as measured by completion of both technical and nontechnical tasks, in simulated extracorporeal membrane oxygenation emergencies [15 ▪ ]. Interestingly, in the control arm of this study (no checklist), three-person teams performed better than two-person teams; teams exposed to the intervention (checklist use) outperformed the control arm regardless of team size, and two- and three-person teams using the checklist performed equally well.…”
Section: Evidence Supporting Cognitive Aid Usementioning
confidence: 99%